Laboratory Training in Bifrontal and Frontolateral Approaches Using Cadaveric Silicone-Injected Cow Craniums - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2015)
Background: A microneurosurgical laboratory training model was designed for trainees in neurosurgery to help them to learn how to handle surgical microscopes and microneurosurgical instruments. A silicone-injected fresh cadaveric cow cranium is a suitable alternative to using a cadaveric human brain for gaining familiarity with the frontal cranial nerves and vascular structures for bifrontal and frontolateral approaches. Methods: A silicone-injected cadaveric cow cranium was prepared by irrigating the major vessels, followed by the injection of silicone colored either red or blue. Results: A three-step approach was designed to simulate microneurosurgical dissection along the frontal lobe and for the dissection of cranial nerves and vascular structures. This laboratory training model is useful for trainees to gain experience in the use of an operating microscope and become more familiar with the anterior neural and vascular structures in bifrontal and frontolateral approaches. Conclusion: The aim of this study was to develop an innovative model to create a life-like microneurosurgical training system. This model simulates bifrontal and frontolateral approaches performed on the human brain.
Keywords: Cadaver; anterior vascular structures; silicone injection; cow cranium; microneurosurgical training; resident training; MODEL; BRAIN; SURGERY